2017
DOI: 10.1038/s41598-017-16255-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxamine improves survival and limits cardiac dysfunction after MI

Abstract: Advanced glycation end products (AGEs) play a key role in the progression of heart failure. Whether treatments limiting AGEs formation would prevent adverse left ventricular remodeling after myocardial infarction (MI) remain unknown. We investigated whether pyridoxamine (PM) could limit adverse cardiac outcome in MI. Rats were divided into MI, MI + PM and Sham. Echocardiography and hemodynamic parameters were used to assess cardiac function 8 weeks post-surgery. Total interstitial collagen, collagen I and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Whether an improved diastolic function related to a decreased fibrosis content following exercise training can be completely ruled out remains to be further confirmed as it has been shown that diastolic function ( i.e . EDP) is directly associated with cardiac fibrosis level 40,41 . However, most experiments examining fibrosis and diastolic function have been performed under pathological settings 39,42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether an improved diastolic function related to a decreased fibrosis content following exercise training can be completely ruled out remains to be further confirmed as it has been shown that diastolic function ( i.e . EDP) is directly associated with cardiac fibrosis level 40,41 . However, most experiments examining fibrosis and diastolic function have been performed under pathological settings 39,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior to sacrifice, transthoracic echocardiography was performed under 2% isoflurane in all animals with a Vivid I ultrasound machine (GE Vingmed Ultrasound) using a 10 MHz linear array transducer. The protocol used is as described previously 40,41 . Briefly, a standard parasternal long axis image and short axis views at the mid-ventricular level were obtained at a temporal resolution of approximately 200 frames per second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we observed an increase in collagen type I and collagen type III in HMW-AGEs-injected animals, the predominant subtypes of collagen in artery walls 54 . This increase in interstitial collagen deposition and the content of collagen subtypes has also been observed in the hearts of rats with myocardial infaction (MI) 14 . Interestingly, the increase of collagen deposition with MI was reduced after administering the AGEs-formation inhibitor pyridoxamine.…”
Section: Discussionmentioning
confidence: 59%
“…nephropathy, neuropathy and retinopathy) complications of diabetes 11 , 12 . Despite optimistic results on the use of anti-AGEs therapies such as aminoguanidine, pyridoxamine, and alagebrium in animal models of increased LMW-AGEs 13 , 14 , clinical evidence on their safety and efficacy is currently weak, suggesting the involvement of other AGEs entities 15 . Previous research has mainly focused on mature LMW-AGEs compounds such as pentosidine and carboxymethyllysine (CML) or their precursors such as methylglyoxal, while the contribution of HMW-AGEs to cardiovascular dysfunction is largely unknown.…”
Section: Introductionmentioning
confidence: 99%